Manifestaciones orales y su manejo odontológico en pacientes con enfermedades autoinmunes. Revisión sistemática de la literatura (2023)
Autoimmune diseases are pathologies in which the immune system loses the ability to distinguish between its own and foreign components, which leads to the body's own cells and tissues being attacked by the immune system.